Prognostic significance of combined MN1, ERG, BAALC, and EVI1 (MEBE) expression in patients with myelodysplastic syndromes - Thol, Felicitas; Hofmann, Wolf-Karsten (Annals of hematology, 2012)
Overexpression of MN1, ERG, BAALC, and EVI1 (MEBE) genes in cytogenetically normal acute myeloid leukemia (AML) patients is associated with poor prognosis, but their prognostic effect in patients with myelodysplastic syndromes (MDS) has not been studied systematically. Expression data of the four genes from 140 MDS patients were combined in an additive score, which was validated in an independent patient cohort of 110 MDS patients. A high MEBE score, defined as high expression of at least two of the four genes, predicted a significantly shorter overall survival (OS) (HR 2.29, 95 % CI 1.3-4.09, P = .005) and time to AML progression (HR 4.83, 95 % CI 2.01-11.57, P < .001) compared to a low MEBE score in multivariate analysis independent of karyotype, percentage of bone marrow blasts, transfusion dependence, ASXL1, and IDH1 mutation status. In a validation cohort of 110 MDS patients, a high MEBE score predicted shorter OS (HR 1.77; 95 % CI 1.04-3.0, P = .034) and time to AML progression (HR 3.0, 95 % CI 1.17-7.65, P = .022). A high MEBE expression score is an unfavorable prognostic marker in MDS and is associated with an increased risk for progression to AML. Expression of the MEBE genes is regulated by FLI1 and c-MYC, which are potential upstream targets of the MEBE signature.